Super-hydrophobic activated carbon adsorption material as well as preparation method and application thereof

By conducting hydrolytic polymerization in an alkaline aqueous solvent, superhydrophobic nanoparticles are formed and coated onto the surface of activated carbon, the problem of pore blockage in the modification process of existing hydrophobic activated carbon materials is solved, and efficient superhydrophobic modification and adsorption performance is achieved.

CN119819263AActive Publication Date: 2025-04-15SHANDONG UNIV +1

Patent Information

Application Number
CN202510189222.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-20
Publication Date
2025-04-15
Estimated Expiration
2045-02-20

AI Technical Summary

Technical Problem

In the modification process of existing hydrophobic activated carbon materials, a large number of modifiers and solvents are usually used, resulting in blockage of the activated carbon pore structure and reducing the adsorption capacity.

Method used

Superhydrophobic modification is achieved by performing hydrolysis polymerization reaction in an alkaline aqueous solvent, superhydrophobic nanoparticles are used to form superhydrophobic nanoparticles and organic silanes, and coated onto the surface of activated carbon.

Benefits of technology

This method not only reduces the cost of hydrophobic modification of activated carbon and enhances its hydrophobic properties, but also retains the adsorption capacity of activated carbon and improves the adsorption selectivity of humid VOCs exhaust gas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819263A_ABST
    Figure CN119819263A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of functional activated carbon materials, and relates to a super-hydrophobic activated carbon adsorption material as well as a preparation method and application thereof. The preparation method comprises the following steps: carrying out hydrolytic polymerization reaction on hydroxyl-containing nanoparticles and organosilane in an alkaline water-containing solvent to obtain the super-hydrophobic nanoparticles, and coating the surface of the activated carbon with the super-hydrophobic nano-particles to obtain the super-hydrophobic activated carbon. Wherein the chemical structural formula of the organosilane is as follows: # imgabs0 # R1 is straight chain alkyl of C10-C20, and R2, R3 and R4 are alkoxy or halogen of C1-C5. The super-hydrophobic activated carbon adsorption material provided by the invention not only has excellent super-hydrophobic performance, but also can avoid blockage of pores of activated carbon, has excellent adsorption performance, and can be widely applied to the field of adsorption treatment of volatile organic compounds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of functional activated carbon materials and relates to a super hydrophobic activated carbon adsorption material and a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] With the continuous development of the chemical industry, the emission of volatile organic compounds (VOCs) has increasingly attracted widespread attention from all walks of life. VOCs have the characteristics of low boiling point, high vapor pressure and easy volatility. The potential threat they pose to the ecological environment and human health has been widely confirmed by the scientific community. The adsorption method has been widely used due to its significant advantages such as high treatment efficiency and low operating cost. Among them, activated carbon, as the most traditional adsorption material, has become the most common VOCs adsorption material due to its high specific surface area, developed pore structure, low cost and easy recovery. However, due to different process types and climatic conditions, the discharged VOCs waste gas will contain more or less water vapor. In the adsorption treatment process of VOCs, due to the rich oxygen-containing functional groups on the surface of activated carbon, water vapor will preferentially occupy the adsorption sites of activated carbon, thereby seriously reducing the adsorption capacity of activated carbon for VOCs. Therefore, it is necessary to perform a certain degree of hydrophobic treatment on activated carbon to overcome the limitation of poor adsorption performance of activated carbon for wet VOCs waste gas.

[0004] In recent years, researchers have used various methods to hydrophobically modify activated carbon materials and applied them to the adsorption of VOCs, thereby reducing the competitive adsorption of water molecules and VOCs molecules on activated carbon. However, the inventors have found that in the prior art, most hydrophobic activated carbon materials are directly grafted with modifiers (such as silane coupling agents, long carbon chain organic acids, etc.) on the surface of activated carbon. This method usually uses a large amount of modifiers and solvents, and also causes blockage of the pore structure of activated carbon, reducing the adsorption capacity of activated carbon. Summary of the invention

[0005] In order to overcome the deficiencies in the prior art, the object of the present invention is to provide a super hydrophobic activated carbon adsorption material and a preparation method and application thereof. The super hydrophobic activated carbon adsorption material provided by the present invention not only has excellent super hydrophobic properties, but also can avoid clogging of the activated carbon pores, has excellent adsorption properties, and can be widely used in the field of adsorption treatment of volatile organic compounds (VOCs).

[0006] In order to achieve the above object, the technical solution of the present invention is:

[0007] In a first aspect, a method for preparing a super hydrophobic activated carbon adsorption material comprises the following steps:

[0008] In an alkaline aqueous solvent, the hydroxyl-containing nanoparticles undergo a hydrolysis polymerization reaction with the organosilane to obtain superhydrophobic nanoparticles;

[0009] The super-hydrophobic nanoparticles are coated on the surface of activated carbon to obtain;

[0010] Wherein, the chemical structural formula of the organosilane is: R1 is a C10-C20 straight chain alkyl group, and R2, R3, and R4 are C1-C5 alkoxy groups or halogen groups.

[0011] At present, the method of modifying activated carbon into hydrophobic activated carbon mainly involves loading hydrophobic groups on the surface of activated carbon or removing hydrophilic groups. However, the hydrophobic activated carbon prepared by these methods mainly uses modifiers to directly chemically modify the activated carbon in a solvent, usually using a large amount of solvents and modifiers, which also causes blockage of the pore structure of the activated carbon and reduces the adsorption capacity of the activated carbon.

[0012] The present invention is in hydrolysis polymerization reaction, organosilane is first hydrolyzed to form silanol, the hydroxyl of hydroxyl nanoparticles can be active site, chemical grafting and bonding are carried out with the formation of silanol, and the organosilane with hydrophobic long carbon chain is polymerized under alkaline conditions, so that the hydrophobic long carbon chain is firmly fixed on the surface of hydroxyl nanoparticles, to form super-hydrophobic nanoparticles, and then the super-hydrophobic nanoparticles are coated on the surface of activated carbon, due to van der Waals force, electrostatic attraction, and the hydrophobic interaction between the hydrophobic long carbon chain and the hydrophobic carbon structure on the surface of activated carbon, so that the super-hydrophobic nanoparticles can be closely fitted on the surface of activated carbon, reducing the difficulty of super-hydrophobic material attached to the surface of activated carbon, so as to ensure the super-hydrophobic performance of the super-hydrophobic activated carbon adsorption material, and enhance the repellency of activated carbon to water vapor. At the same time, the method will not block the internal pore structure of activated carbon, and the nanoparticle coating attached to the surface of activated carbon re-aggregates to form a new pore structure, increases the specific surface area of ​​activated carbon, retains the adsorption performance of activated carbon, and enhances the adsorption selectivity of activated carbon to moist VOCs waste gas.

[0013] In a second aspect, a super hydrophobic activated carbon adsorption material is obtained by the above preparation method.

[0014] In a third aspect, a super hydrophobic activated carbon adsorption material is used for adsorption of VOCs in a humid environment.

[0015] The beneficial effects of the present invention are:

[0016] The super-hydrophobic activated carbon adsorption material prepared by the present invention is firstly prepared by hydrolyzing and polymerizing an organic silane on the surface of a hydroxyl-containing nanoparticle to obtain super-hydrophobic nanoparticles, and then coating the surface of activated carbon to obtain the super-hydrophobic nanoparticles. Hexadecyltrimethoxysilane is hydrolyzed and polymerized on the surface of the hydroxyl-containing nanoparticles under alkaline conditions, so that the hydroxyl-containing nanoparticles are grafted with a large number of hydrophobic long carbon chains, and the super-hydrophobic modification of the activated carbon is achieved through simple coating. The method is simple to operate and low in price. The modified activated carbon has excellent hydrophobic performance and can be widely used in the field of adsorption of volatile organic compounds (VOCs) in a humid environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0018] Figure 1 This is a scanning electron microscope image of the super hydrophobic activated carbon obtained in Example 1 of the present invention;

[0019] Figure 2 This is a scanning electron microscope image of the activated carbon of Comparative Example 1 of the present invention;

[0020] Figure 3 This is a water contact angle diagram of the super hydrophobic activated carbon obtained in Example 1 of the present invention;

[0021] Figure 4 This is a water contact angle diagram of the activated carbon of Comparative Example 1 of the present invention;

[0022] Figure 5 This is a wetting state diagram of the super hydrophobic activated carbon obtained in Example 1 of the present invention and the comparative example 1 after being put into water;

[0023] Figure 6 The nitrogen adsorption-desorption curves of the super hydrophobic activated carbon obtained in Example 1 of the present invention and Comparative Example 1 are shown;

[0024] Figure 7 It is a penetration curve diagram of toluene adsorption of the super hydrophobic activated carbon obtained in Example 1 of the present invention and the comparative example 1 under a relative humidity of 0%.

[0025] Figure 8 It is a penetration curve diagram of toluene adsorption of the super hydrophobic activated carbon obtained in Example 1 of the present invention and the comparative example 1 under a relative humidity of 80%. DETAILED DESCRIPTION

[0026] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0027] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0028] In view of the fact that the existing methods for hydrophobic modification of activated carbon usually use a large amount of modifiers and solvents, and also cause the pore structure of activated carbon to be blocked, reducing the adsorption capacity of activated carbon, the present invention has found that by simply spraying super-hydrophobic hydroxyl-containing nanoparticles to super-hydrophobically modify activated carbon, not only the cost of hydrophobic modification of activated carbon is reduced, the hydrophobic properties of activated carbon are effectively improved, and the specific surface area of ​​activated carbon is increased. Therefore, the present invention proposes a super-hydrophobic activated carbon adsorption material and its preparation method and application.

[0029] A typical embodiment of the present invention provides a method for preparing a super hydrophobic activated carbon adsorption material, comprising the following steps:

[0030] In an alkaline aqueous solvent, the hydroxyl-containing nanoparticles undergo a hydrolysis polymerization reaction with the organosilane to obtain superhydrophobic nanoparticles;

[0031] The super-hydrophobic nanoparticles are coated on the surface of activated carbon to obtain;

[0032] Wherein, the chemical structural formula of the organosilane is: R1 is a C10-C20 straight chain alkyl group, and R2, R3, and R4 are C1-C5 alkoxy groups or halogen groups.

[0033] In the organosilane of the present invention, R2, R3, and R4 may be the same or different. In some embodiments, R2, R3, and R4 are methoxy, ethoxy, or chlorine.

[0034] In some embodiments, the organosilane is one or a combination of dodecyltrichlorosilane, tetradecyltrichlorosilane, hexadecyltrichlorosilane, octadecyltrichlorosilane, dodecyltrimethoxysilane, tetradecyltrimethoxysilane, hexadecyltrimethoxysilane, octadecyltrimethoxysilane, dodecyltriethoxysilane, dodecyltriethoxysilane, tetradecyltriethoxysilane, and octadecyltriethoxysilane.

[0035] In some embodiments, the hydroxyl-containing nanoparticles are one or a combination of nano-silicon dioxide, nano-titanium dioxide, nano-zirconium dioxide and nano-hydroxyapatite. The size of the hydroxyl-containing nanoparticles is 5-100 nm.

[0036] In some embodiments, the hydroxyl-containing nanoparticles are added to an alcohol solvent and dispersed uniformly, water is added, and the pH of the solvent system is adjusted to be alkaline, and then an organosilane is added to react. In order to make the hydroxyl-containing nanoparticles disperse uniformly in the alcohol solvent, specifically, ultrasonic dispersion is adopted. The alcohol solvent of the present invention is a liquid alcohol organic substance, such as methanol, ethanol, propanol, ethylene glycol, etc., which is miscible with water and is conducive to the reaction.

[0037] In some embodiments, the mass ratio of the organosilane to the hydroxyl-containing nanoparticles is (0.7-1.0):1.

[0038] In some embodiments, the pH value of the alkaline aqueous solvent is between 9 and 11. The pH of the alkaline aqueous solvent is adjusted using aqueous ammonia.

[0039] In some embodiments, the mass ratio of the added water to the mass ratio of the hydroxyl-containing nanoparticles is (1-2):1.

[0040] In some embodiments, the reaction time is 1 to 6 hours.

[0041] The activated carbon of the present invention is non-powdered activated carbon, which is conducive to the coating of super-hydrophobic nanoparticles on the surface of the activated carbon. In some embodiments, the activated carbon is one or more of cylindrical activated carbon, granular activated carbon or clover-shaped activated carbon.

[0042] In some embodiments, the method of coating the super-hydrophobic nanoparticles on the surface of the activated carbon is spraying. By spraying the super-hydrophobic nanoparticles directly onto the surface of the activated carbon, the super-hydrophobic modification of the activated carbon can be achieved with a small amount of raw materials, the amount of super-hydrophobic nanoparticles used can be reduced, and the porosity of the prepared super-hydrophobic activated carbon adsorption material can be further increased.

[0043] In one or more embodiments, during the spraying process, the distance between the spray gun nozzle and the activated carbon is 10-20 cm, the spraying pressure (pressure) is 0.3-1 MPa, and the moving speed is 2-5 cm / s.

[0044] Another embodiment of the present invention provides a super hydrophobic activated carbon adsorption material obtained by the above preparation method.

[0045] A third embodiment of the present invention provides an application of the above-mentioned super-hydrophobic activated carbon adsorption material in the field of VOCs adsorption.

[0046] In some embodiments, the relative humidity of the environment where VOCs are adsorbed is above 60%.

[0047] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.

[0048] Example 1

[0049] 1 g of 30 nm silica was added to 80 g of anhydrous ethanol and ultrasonically dispersed for 10 min. The mixture was magnetically stirred for 10 min. 1 g of water was added. Ammonia water was added to adjust the pH to 10. 1 g of hexadecyltrimethoxysilane was added and magnetically stirred for 2 h to obtain a superhydrophobic nano-silica suspension.

[0050] The super-hydrophobic nano-silica suspension was added to the spray gun and sprayed onto the surface of the cylindrical wood activated carbon. The distance between the spray gun and the activated carbon was 15 cm, the spraying pressure was 0.5 MPa, the moving speed was 3 cm / s, and the mixture was air-dried at room temperature for 6 h to obtain super-hydrophobic activated carbon.

[0051] The scanning electron microscope images of the super hydrophobic activated carbon obtained in Example 1 of the present invention and Comparative Example 1 are as follows: Figure 1-2 As shown, the surface of the original activated carbon in Comparative Example 1 is relatively smooth and uniform in morphology. After uniform spraying, the mutually aggregated super-hydrophobic nano-silica is deposited on the surface of the activated carbon, forming a rich pore structure and nano-level roughness. Figure 3-4 The water contact angle diagram of the super hydrophobic activated carbon obtained in Example 1 of the present invention and the comparative example 1 is shown in Figure 1. The water contact angle values ​​are 162.4° and 0° respectively. After the super hydrophobic modification by a simple spraying method, the activated carbon achieves a transformation from super hydrophilicity to super hydrophobicity. The wetting state diagram of the super hydrophobic activated carbon obtained in Example 1 of the present invention and the comparative example 1 after being put into water is shown in Figure 1. Figure 5 As shown in the figure, due to the super hydrophilicity of the original activated carbon, water quickly occupied its pores and thoroughly infiltrated it before settling to the bottom of the container. However, due to the super hydrophobic multi-cavity nanostructure on the surface of the super hydrophobic activated carbon, it captured a layer of air as a protective layer and floated on the water surface after contacting with water. Figure 6 The nitrogen adsorption-desorption curves of the super hydrophobic activated carbon obtained in Example 1 of the present invention and the comparative example 1 are shown in Figure 1. The super hydrophobic modification by spraying method did not block the pores of the activated carbon and did not change the pore structure. The BET specific surface areas before and after modification were 895 m 2 / g and 949m 2 / g, and the BET specific surface area increased instead of decreased. This is because the nano-silica particles aggregated on the surface of the activated carbon to form a new pore structure.

[0052] Example 2

[0053] The difference between this embodiment and embodiment 1 is that, except for adjusting the 30 nm size of silicon dioxide to 50 nm size of silicon dioxide, the rest is the same as embodiment 1.

[0054] Example 3

[0055] The difference between this embodiment and embodiment 1 is that, except that the 30 nm size of silicon dioxide is adjusted to 20 nm size of titanium dioxide, the rest is the same as embodiment 1.

[0056] Example 4

[0057] The difference between this embodiment and embodiment 1 is that, except that the 30 nm size silicon dioxide is adjusted to 50 nm size zirconium dioxide, the rest is the same as embodiment 1.

[0058] Example 5

[0059] The difference between this embodiment and embodiment 1 is that, except that the 30 nm size of silicon dioxide is adjusted to 20 nm size of hydroxyapatite, the rest is the same as embodiment 1.

[0060] Example 6

[0061] The difference between this embodiment and embodiment 1 is that, except that the cylindrical wood activated carbon is adjusted to clover-shaped coconut shell activated carbon, the rest is the same as embodiment 1.

[0062] Example 7

[0063] The difference between this embodiment and embodiment 1 is that, except that the mass ratio of the hexadecyltrimethoxysilane to the 30 nm silicon dioxide is adjusted to 0.8:1, the rest is the same as embodiment 1.

[0064] Comparative Example 1

[0065] This comparative example provides a cylindrical wood activated carbon, and the cylindrical wood activated carbon is not subjected to any modification treatment.

[0066] Performance Testing

[0067] Table 1 shows the adsorption performance test data of toluene of the activated carbon before and after modification in Comparative Example 1 under relative humidity of 0% and 80%.

[0068] Table 1

[0069]

[0070] Figure 7 and Figure 8 They are penetration curves of toluene adsorption by the super hydrophobic activated carbon obtained in Example 1 of the present invention and Comparative Example 1 under relative humidity of 0% and 80%, respectively.

[0071] Combination Figure 7 , Figure 8As can be seen from Table 1, at 0%RH, the adsorption capacity of toluene in Comparative Example 1 is basically the same as that in Example 1, because the pores of the activated carbon obtained by the super-hydrophobic modification of the spraying method are not blocked. When the relative humidity increases to 80%, the adsorption capacity of Comparative Example 1 decreases by 47%, because there are abundant oxygen-containing functional groups on the surface of the activated carbon, and water molecules will occupy a large number of adsorption sites of the activated carbon, forming competitive adsorption with toluene. However, at 80%RH, the adsorption capacity of toluene by the super-hydrophobic activated carbon obtained in Example 1 is only reduced by 16%, because the super-hydrophobic nano-silica barrier on the surface of the super-hydrophobic activated carbon resists most of the water vapor, making it impossible to occupy the adsorption sites inside the activated carbon, and the super-hydrophobic modification makes the activated carbon enhance the selective adsorption of VOCs. It can be seen from the above results that the super-hydrophobic activated carbon obtained by the present invention not only has a low modification cost, but also has excellent adsorption performance for VOCs in a humid environment, and has broad industrial application prospects.

[0072] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a super hydrophobic activated carbon adsorption material, comprising: The process is as follows: In an alkaline aqueous solvent, the hydroxyl-containing nanoparticles undergo a hydrolysis polymerization reaction with the organosilane to obtain superhydrophobic nanoparticles; The super-hydrophobic nanoparticles are coated on the surface of activated carbon to obtain; Wherein, the chemical structural formula of the organosilane is: R1 is a C10-C20 straight chain alkyl group, and R2, R3, and R4 are C1-C5 alkoxy groups or halogen groups.

2. The method for preparing a super hydrophobic activated carbon adsorption material according to claim 1, wherein: R2, R3, R4 are methoxy, ethoxy or chlorine; Or, the organosilane is one or a combination of dodecyltrichlorosilane, tetradecyltrichlorosilane, hexadecyltrichlorosilane, octadecyltrichlorosilane, dodecyltrimethoxysilane, tetradecyltrimethoxysilane, hexadecyltrimethoxysilane, octadecyltrimethoxysilane, dodecyltriethoxysilane, dodecyltriethoxysilane, tetradecyltriethoxysilane, and octadecyltriethoxysilane.

3. The method for preparing a super hydrophobic activated carbon adsorption material according to claim 1, wherein: The hydroxyl-containing nanoparticles may be one or a combination of nano silicon dioxide, nano titanium dioxide, nano zirconium dioxide and nano hydroxyapatite.

4. The method for preparing a super hydrophobic activated carbon adsorption material according to claim 1, wherein: The hydroxyl-containing nanoparticles are added to an alcohol solvent and dispersed uniformly, water is then added, and the pH of the solvent system is adjusted to be alkaline, and then organic silane is added to react.

5. The method for preparing a super hydrophobic activated carbon adsorption material according to claim 1, wherein: The mass ratio of organosilane to hydroxyl-containing nanoparticles is (0.7-1.0):1; or, the pH value of the alkaline aqueous solvent is 9 to 11; Or, the mass ratio of the added water to the mass ratio of the hydroxyl-containing nanoparticles is (1-2):1; Alternatively, the reaction time is 1 to 6 hours.

6. The method for preparing a super hydrophobic activated carbon adsorption material according to claim 1, wherein: The activated carbon is one or more of cylindrical activated carbon, granular activated carbon or clover-shaped activated carbon.

7. The method for preparing a super hydrophobic activated carbon adsorption material according to claim 1, wherein: The method of coating the superhydrophobic nanoparticles onto the activated carbon surface is spraying; Preferably, during the spraying process, the distance between the spray gun nozzle and the activated carbon is 10-20 cm, the spraying pressure is 0.3-1 MPa, and the moving speed is 2-5 cm / s.

8. A super hydrophobic activated carbon adsorption material, characterized in that: Obtained by the preparation method according to any one of claims 1 to 7.

9. Use of the super hydrophobic activated carbon adsorption material according to claim 8 in the field of VOCs adsorption.

10. The use according to claim 10, characterized in that: The relative humidity of the environment in which VOCs are adsorbed is above 60%.

Citation Information

Patent Citations

  • Fluorine-free waterproof moisture-proof super-hydrophobic activated carbon as well as preparation method and application thereof

    CN114408924A

  • Super-hydrophobic activated carbon material as well as preparation method and application thereof

    CN116081623A

  • Hydrophobic activated carbon as well as preparation method and application thereof

    CN117548085A

  • Super-hydrophobic activated carbon coating material as well as preparation method and application thereof

    CN119075939A

  • Core-shell type hydrophobic modified activated carbon and preparation method thereof

    CN119409192A

Cited By

  • Preparation method of transition metal doped hierarchical porous carbon applied to co-adsorption of multiple VOCs (Volatile Organic Compounds)

    CN120679485A

  • A preparation method of metal-doped multi-level porous carbon applied to co-adsorption of various VOCs

    CN120679485B